Humanising artificial intelligence: what so wrong about It? - Saleh, Abdulmajid Obaid Hasan; Mohd. Zain, Nor Razinah; Mohd Noor, Azman (Universiti Putra Malaysia, 2021)
Artificial intelligence is a created machine intelligence different from natural intelligence. Nowadays, artificial intelligence is celebrated as one of the most advanced technological achievement in modern civilisation. Such position influences a movement to place artificial intelligence as a preference due to its existing benefits. At the same time, certain opinions emphasise celebrating artificial intelligence in a parallel, similar or more advanced than natural intelligence as bestowed to humankind. This research looks deeper into the intellectual discourse of giving human rights to artificial intelligence as enforceable rights based on the qualitative investigation. Based on a comparative analysis between the existing laws and principles of Shariah, this research also looks into the status of artificial intelligence and the relevancy of authorising such human rights to it. Artificial intelligence is a machine intelligence created by humans. Thus, it is a mechanical tool that depends on machine learning and computerised system ability. It is inadequate to impose human rights on such mechanical tool. The imposition of rights must be supported with relevant and qualified legal reasons and not merely based on created rights. Such practice may lead to deviation and abuse of existing rights while transgressing the real receiver of rights.